Salmonellosis Presenting with Septic Arthritis and Osteomyelitis: A Case Report - Dias Figueiredo, Rita; M. Abreu, Joana; Lança Pereira, João; Lázaro Mendes, João; Nascimento, Edite (Futurity Medicine, 2026)
Aims: To describe an unusual and severe presentation of non-typhoidal salmonellosis involving multiple atypical anatomical sites in an elderly immunocompromised patient, and to highlight the diagnostic and therapeutic challenges associated with this condition. Study Design: Single case report. Place and Duration of Study: The case was managed at a tertiary care hospital. The patient was followed from initial presentation at the emergency department through surgical intervention and outpatient orthopedic follow-up, over a period of approximately four months. Methodology: Clinical data were obtained from the patient’s medical records, including laboratory results, microbiological cultures, imaging studies, surgical reports, and outpatient follow-up records. Results: A woman in her 80s, immunocompromised due to prolonged corticosteroid therapy for organizing pneumonia, presented with right inguinal pain and functional limitation of gait, without fever or gastrointestinal symptoms. Blood and urine cultures were positive for non-typhoidal Salmonella group D. Despite targeted antibiotic therapy, inflammatory markers worsened. Advanced imaging revealed right iliopsoas abscesses, septic arthritis, and osteomyelitis of the right proximal femur. Management included an eight-week course of ampicillin combined with proximal femoral osteotomy, surgical joint debridement, and placement of antibiotic-loaded spacers, followed by total right hip arthroplasty. The patient showed favourable clinical and laboratory evolution. Conclusion: This case highlights the potential for non-typhoidal Salmonella to cause severe disseminated infection involving atypical anatomical sites, particularly in immunocompromised patients and even without classic gastrointestinal symptoms. Early microbiological diagnosis, advanced imaging, and a multidisciplinary approach are essential when response to initial antibiotic therapy is inadequate.